Cold cereal - Rex, Adam. (a Cold cereal saga ;, 2012)
A boy who may be part changeling, twins involved in a bizarre secret experiment, and a clurichaun in a red tracksuit try to save the world from an evil cereal company whose ultimate goal is world domination.